1994
DOI: 10.1095/biolreprod51.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Rat Prostate Gland is Facilitated by the Autonomic Nervous System1

Abstract: Many factors are implicated in the development of prostatic growth: androgens, growth factors, and stromo-epithelial interaction. This study examines the role of the sympathetic and parasympathetic branches of the autonomic nervous system control of different aspects of rat prostate growth and atrophy. Unilateral sympathectomy leads to decreases in ventral prostate weight, DNA, and protein content in the lesioned side. Unilateral parasympathectomy leads to increases in ventral prostate weight, DNA, and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
1
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(125 citation statements)
references
References 32 publications
5
114
1
5
Order By: Relevance
“…34 Rat models have demonstrated an effect on prostatic growth and differentiation through manipulation of autonomic activity. 35 Not only can changes at the level of adrenergic receptor expression and circulating sympathetic neurotransmitters explain a link between ED and LUTS, but also changes at the level of the myosinactin filament interaction leading to smooth muscle hypercontractility have further been described in both diseases. Contraction of smooth muscle is stimulated by the inhibition of myosin light chain phosphatase by Rho kinase, and, therefore, provides a calcium-independent mechanism for smooth muscle contraction.…”
Section: Luts and Ed: Pathophysiological Correlationsmentioning
confidence: 99%
“…34 Rat models have demonstrated an effect on prostatic growth and differentiation through manipulation of autonomic activity. 35 Not only can changes at the level of adrenergic receptor expression and circulating sympathetic neurotransmitters explain a link between ED and LUTS, but also changes at the level of the myosinactin filament interaction leading to smooth muscle hypercontractility have further been described in both diseases. Contraction of smooth muscle is stimulated by the inhibition of myosin light chain phosphatase by Rho kinase, and, therefore, provides a calcium-independent mechanism for smooth muscle contraction.…”
Section: Luts and Ed: Pathophysiological Correlationsmentioning
confidence: 99%
“…Rat models have shown that manipulation of autonomic activity leads to effects on prostatic growth and differentiation. 49 In aging rats, the development of BPH and ED were promoted by increased autonomic nervous system activity. 50 In addition, hyperlipidemic rats, fed a high fat diet, develop prostatic enlargement, bladder overactivity, and ED.…”
Section: Ah and The Metabolic Syndromementioning
confidence: 99%
“…It is known that autonomic nervous system innervation is important for the control of prostate glandular growth and differentiation, as witnessed by the observations that sympathectomy results in a reduction of prostate volume, 83 while spontaneously hypertensive rats that have increased autonomic activity also develop BPH. 84 Given our understanding of the autonomic nervous system in modulating aspects of physiology in response to 'stress', it is plausible that hyperactivity could play a more direct role in altered voiding and erectile function.…”
Section: Autonomic Hyperactivitymentioning
confidence: 99%